Food preferences and thyroid hormones in children and adolescents with obesity - Staníková, Daniela; Krajčovičová, Lea; Demková, Linda; Forišek-Paulová, Petronela; Slobodová, Lucia; Vitariušová, Eva; Tichá, Lubica; Ukropcová, Barbara; Staník, Juraj; Ukropec, Jozef (Frontiers in Psychiatry, 2022)
Background. Thyroid hormones profoundly affect energy metabolism but their interrelation with food preference, which might contribute to childhood obesity development, are much less understood. Here we investigated if thyroid hormone levels are associated with specific modulation of food preference and potentially linked to the level of obesity in children and adolescents. Methods. Interrelations between food preference and peripheral thyroid activity were examined in a population of 99 non-obese and 101 obese children and adolescents (12.8±3.6 yrs. of age, 111/89 F/M) randomly selected from the patients of Obesity and Metabolic Disease Out-patient Research unit at National Institute for Children´s Diseases in Bratislava in a period between 12/2017 and 3/2020. Results. Children and adolescents with obesity had lower preference for food rich in high sucrose and high-complex carbohydrates, while the preference for protein and fat-containing food and that for dietary fibers did not differ between obese and non-obese. In adolescents with obesity, free thyroxine (FT4) correlated positively with the preference for high protein, high fat rich diet, irrespective of the fatty acid unsaturation level. Moreover, FT4 correlated negatively with the preference for dietary fibers which has been also exclusively found in obese adolescents. Individuals with obesity with higher FT4 levels had higher systemic levels of AST and ALT then the population with lower FT4. Multiple regression analysis with age, sex, BMI-SDS and FT4 as co-variates revealed that FT4 and male gender are the major predictors of variability in the preference for diet high in protein, fat and monounsaturated fatty acids. FT4 was the sole predictor of the preference for diet containing saturated and polyunsaturated fatty acids as well as for diet low in fibers. Conclusions. The link between free thyroxin levels and dietary preference for food rich in fat and protein is present exclusively in individuals with obesity. Higher serum FT4 was linked with elevated AST and ALT in children and adolescentrs with obesity, and FT4 was the best predictor for preference for food rich in fat and low in fiber. This may indicate that FT4 could contribute to the development of childhood obesity and its complications by modulating food preference.